(untitled) (Pedagogical Horizons, 2024)
As part of ’Pädagog:innenbildung NEU’, teacher training courses have followed the Bologna structure since 1st October 2014. However, this increase in the duration of studies has intensified the debate about the benefits of academic theory for school practice. It is not uncommon for the length of the programme to not only be criticised, but also fundamentally questioned. The aim of this article is to highlight the inherent theory-practice problem of pedagogy by means of historical reassurance in order to draw conclusions for pedagogical professional competence on the one hand and to focus on the added value of academic writing and research on the other. The empirical study using qualitative expert interviews is intended to show the benefits of academic work in the study of education, but also to provide impulses for the upcoming curricular restructuring in the academic year 2025/26. The results show that in-depth academic specialisation leads to a changed (pedagogical) perspective and a research-based attitude. Contingent situations of pedagogical practice and children’s behaviour become (more) comprehensible as a result - which not least makes it easier to form practical judgements. In addition to more professional competence, scientific work is effective if research competence is applied. This means that teaching can be researched and positively influenced.